2016
DOI: 10.1021/acsbiomaterials.6b00197
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Targeting and Selective Killing of T47D Breast Cancer Cells by Purpurin and 5-Fluorouracil Anchored to Magnetic CNTs: Nitrene-Based Functionalization versus Uptake, Cytotoxicity, and Intracellular Fate

Abstract: Fe-encapsulated multiwall carbon nanotubes (Fe@MWCNTs) are candidates for magnetically targeted Drug Delivery Systems (mt-DDSs) against breast cancer. However, their full potential as versatile and biosafe vectors has yet to be developed. Key challenges that remain are relating surface functionalization to cytotoxicity and inducing selective cytotoxicity to cancer cells. We have studied quantitative uptake of pristine and functionalized Fe@MWCNTs (f-Fe@MWCNTs) in correlation to their in vitro cytotoxicity. Hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
(89 reference statements)
2
17
0
Order By: Relevance
“…The observations were possible because all of the hybrids exhibited fluorescence in the spectral range of 4 ,6-diamidino-2-phenylindole (DAPI). It was found that "drug-nanotube" hybrids landed, pierced, or in a few cases penetrated cancer cells, similar to our previous studies [42], and the fluorescent drugs were unloaded intracellularly, mainly by diffusion after enzymatic cleavage or physical unloading. The enhanced cell penetration by nanotubes, also in the presence of magnetic field and noncytotoxic to human monocyte macrophage cells, was described by Boncel et al [42] and Mahmood et al [55].…”
Section: Drugs and "Drugsupporting
confidence: 86%
See 2 more Smart Citations
“…The observations were possible because all of the hybrids exhibited fluorescence in the spectral range of 4 ,6-diamidino-2-phenylindole (DAPI). It was found that "drug-nanotube" hybrids landed, pierced, or in a few cases penetrated cancer cells, similar to our previous studies [42], and the fluorescent drugs were unloaded intracellularly, mainly by diffusion after enzymatic cleavage or physical unloading. The enhanced cell penetration by nanotubes, also in the presence of magnetic field and noncytotoxic to human monocyte macrophage cells, was described by Boncel et al [42] and Mahmood et al [55].…”
Section: Drugs and "Drugsupporting
confidence: 86%
“…Nanotubes themselves, as vehicles enhancing targeting and revealing its intrinsic cytotoxicity, may be considered as potential platforms in the magnetic drug delivery. The earlier observed magnetic maneuverability [42] was here confirmed by Mössbauer spectroscopy which indicated the presence of Journal of Nanomaterials …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This characteristic was exploited in other studies. 45,46 The weight loss in the range 320-360 C corresponds to thermal decarbonylation in the CNT-CHO, in which formyl groups were covalently attached to the CNT walls. 35 Therefore, functionalization degrees were calculated by a projection of the peak onset and offset points in derivative thermogravimetry (DTG) curves onto the corresponding TGA curves.…”
Section: Thermogravimetric Analysesmentioning
confidence: 99%
“…The controlled release of a drug may lower its side effects and increases its therapeutic effect on tumors. The complexation of 5‐FU or its derivatives (for example tegafur) inside βCD attached to polymeric vectors, carbon materials, or iron oxide nanoparticles, were reported. The in vitro or in vivo studies revealed the therapeutic potential of the designed 5‐FU delivery platforms.…”
Section: Introductionmentioning
confidence: 99%